2016
DOI: 10.14257/ijsia.2016.10.1.29
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced Biometric-Based Three Factors User Authentication Scheme for Multi-server Environments

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In this section, we review the biometric-based three factors user authentication scheme for multi-server environments by Lin et al [14] in 2016. As previous researches, Lin et al demonstrated the security weaknesses of Baruah et al's scheme [13], and proposed an enhanced biometric-based three factor user authentication scheme for multi-server environments using smart card.…”
Section: Review Of Lin Et Al's Schemementioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we review the biometric-based three factors user authentication scheme for multi-server environments by Lin et al [14] in 2016. As previous researches, Lin et al demonstrated the security weaknesses of Baruah et al's scheme [13], and proposed an enhanced biometric-based three factor user authentication scheme for multi-server environments using smart card.…”
Section: Review Of Lin Et Al's Schemementioning
confidence: 99%
“…Recently, Lin et al [14] found that Baruah et al's scheme cannot resist the stolen smart card attack, and proposed an enhanced user authentication scheme. In order to overcome these weaknesses, they used the fuzzy extractor technology [15].…”
Section: Introductionmentioning
confidence: 99%